Results of a Canadian study examining the prevalence and potential for developing compassion fatigue and burnout in radiation therapists. Issue 4 (23rd April 2014) - Gillies, Carol; Bristow, Bonnie; Gallant, Francois; Osmar, Kari; Lange-Mechlen, Irene; Tran, William Tyler
Abstract Objective Caring is a fundamental tenet of healthcare. Caring 'too much' can result in compassion fatigue syndrome and is often linked to burnout and low morale. The objective of this study was to examine compassion fatigue, secondary traumatic stress (STS) and burnout by investigating the relationship between levels of compassion (compassion satisfaction) and STS and burnout. The study also aimed to identify radiation therapist (RTTs) groups who may be at risk for developing (STS) and burnout. Finally, we investigated the level of social support that RTTs receive. Methods RTTs practicing across Canada were invited to participate in an electronic questionnaire. The questionnaire consisted of: demographic information including health-related issues and occupational variables; the Professional Quality of Life Compassion Satisfaction and Fatigue Questionnaire (ProQOL-V) to assess the potential for compassion satisfaction and vulnerability for STS and burnout; and the Multidimensional Scale of Perceived Social Support (MSPSS) to examine the level and sources of social support. A two-way ANOVA was performed to test the statistical significance between varying groups within the study population. A linear regression analysis using potential co-factors was used to test correlations between compassion fatigue, compassion satisfaction and burnout and variables in age, education, years of experience and levels of caring to patients. Results A total of 477 survey responses were received representing a 36% response rate. Results of the regression analyses generally indicate inverse correlations between the risks associated with compassion satisfaction, burnout and STS compared with the independent study variables of age, education, years of experience and levels of caring to patients. It was observed that responses were not linear within subgroups (age groups, education classifications, years of study). Conclusion RTTs practicing in Canada have a substantial social support network and demonstrate high levels of compassion satisfaction in their daily practice. The results of the study indicate that compassion levels are inversely correlated with burnout and compassion fatigue, although some groups may be at higher risk than others. A possible risk catalyst for compassion fatigue and burnout is associated with underdeveloped managerial workplace support programmes.